2020
DOI: 10.1186/s40360-020-00454-x
|View full text |Cite
|
Sign up to set email alerts
|

A new anabolic compound, LLP2A-Ale, reserves periodontal bone loss in mice through augmentation of bone formation

Abstract: Background Currently, there are no effective medications to reverse periodontal disease (PD)-induced bone loss. The objective of this study was to test a new anabolic compound, LLP2A-Ale, or with the combination treatment of mesenchymal stromal cell (MSC), in the treatment of bone loss secondary to PD. Methods PD was induced in mice by placing a ligature around the second right molar. At one week after disease induction, the mice were treated with … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 68 publications
0
3
0
Order By: Relevance
“…Treatment with a combination of MSCs and LLP2A-Ale further increased peripheral skeletal bone formation and bone mass. These results suggested that LLP2A-Ale treatment can be a novel therapeutic option for the treatment of bone resorption caused by periodontitis [238].…”
Section: Effects Of Natural and Synthetic Compoundsmentioning
confidence: 83%
“…Treatment with a combination of MSCs and LLP2A-Ale further increased peripheral skeletal bone formation and bone mass. These results suggested that LLP2A-Ale treatment can be a novel therapeutic option for the treatment of bone resorption caused by periodontitis [238].…”
Section: Effects Of Natural and Synthetic Compoundsmentioning
confidence: 83%
“…The right maxillae were subjected to a micro-computed tomography system (vivaCT 40; SCANCO Medical, Switzerland) with a resolution of 10.5 μm at 75 kVp. The analysis was performed as described previously . Briefly, measurements were made in the interdental region between M1 and M2 or M2 and M3.…”
Section: Methodsmentioning
confidence: 99%
“…The analysis was performed as described previously. 42 Briefly, measurements were made in the interdental region between M1 and M2 or M2 and M3. For quantitative assessment, the amount of vertical bone remaining was calculated according to the methods reported by Park et al 2007.…”
Section: N-(26-dimethylphenyl)-1-((phenylamino)methyl)-9h-pyrido-[34-...mentioning
confidence: 99%